2011
DOI: 10.1016/j.jbiomech.2010.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Support vector machines for detecting age-related changes in running kinematics

Abstract: Age-related changes in running kinematics have been reported in the literature using classical inferential statistics. However, this approach has been hampered by the increased number of biomechanical gait variables reported and subsequently the lack of differences presented in these studies. Data mining techniques have been applied in recent biomedical studies to solve this problem using a more general approach. In the present work, we re-analyzed lower extremity running kinematic data of 17 young and 17 elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 12 publications
6
39
1
1
Order By: Relevance
“…3). These results are similar to previous studies that indicated age-related changes in discrete joint angles are usually observed in the sagittal plane (Fukuchi, Eskofier, Duarte, & Ferber, 2011;Nigg et al, 2012). Interestingly, PC 1 was also 73% loaded on hip joint and pelvis segment angles (Fig.…”
Section: Lower-and Intermediate-order Pcssupporting
confidence: 92%
“…3). These results are similar to previous studies that indicated age-related changes in discrete joint angles are usually observed in the sagittal plane (Fukuchi, Eskofier, Duarte, & Ferber, 2011;Nigg et al, 2012). Interestingly, PC 1 was also 73% loaded on hip joint and pelvis segment angles (Fig.…”
Section: Lower-and Intermediate-order Pcssupporting
confidence: 92%
“…Data on young runners suggest an association between reduced flexibility and enhanced running economy (13, 25, 52). Yet, only a few investigations have measured the biomechanics of runners beyond 65 years of age (21, 22, 34), and none of them report leg stiffness (k leg ). Other biomechanical variables have also been correlated with the metabolic cost of running including average vertical ground reaction force (GRF) (33), braking and propulsive GRF (11), contact time (t c ) (49), and stride frequency (10).…”
Section: Introductionmentioning
confidence: 99%
“…Age and gender were frequently used for pregrouping individuals (Begg and Kamruzzaman, 2005;Eskofier et al, 2011b;Fukuchi et al, 2011). Afterwards, the movement patterns were compared across these predefined groups to determine if there were differences.…”
Section: Introductionmentioning
confidence: 99%